An evaluation of the safety and efficacy of turoctocog alfa for hemophilia A. Issue 4 (2nd April 2020) - Boban, Ana; Hermans, Cedric
ABSTRACT: Introduction : Hemophilia A is an inherited disorder that is characterized by decreased or absent factor (F)VIII and an increased risk of bleeding. Clinical presentation of the severe form of the disease includes spontaneous bleeding into the joints and muscles, while patients with milder forms usually exhibit trauma-associated bleeding. The treatment of hemophilia aims to prevent bleeding. A number of clotting FVIII concentrates are available for managing hemophilia A, which have different safety and efficacy characteristics. Advancements in biotechnology have enabled development of recombinant factor concentrates, which thus minimize the risk of transmitting infectious diseases. Turoctocog alfa (NovoEight®, Novo Nordisk A/S, Bagsvaerd, Denmark) was the first third-generation B-domain truncated recombinant FVIII. Areas covered : The manuscript describes the characteristics of turoctocog alfa, as well as its efficacy and safety for prophylaxis and on-demand treatment for patients with severe hemophilia A without inhibitors. Expert opinion : In clinical trials, turoctocog alfa has demonstrated very good efficacy and safety for the prophylaxis and on-demand treatment of hemophilia A patients, as well as high hemostatic activity during surgery and in managing bleeding episodes. Post-marketing studies and real-life data are anticipated to further reinforce the value of long-term prophylaxis, and estimate the incidence of inhibitors to FVIII.